Contagem diferencial e morfometria de células sanguíneas nos lagartos Ameivula ocellifera (Squamata: Teiidae) e Tropidurus hispidus (Squamata: Tropiduridae) do semiárido brasileiro, com análise dos efeitos por hemoparasitos - Souza Lima, Igor Gabriel (2021)
Differential counting and blood cell morphometry in the lizards Ameivula ocellifera (Squamata: Teiidae) and Tropidurus hispidus (Squamata: Tropiduridae) from the Brazilian semiarid region, with analysis of the effects by hemoparasites. The lizards Ameivula ocellifera and Tropidurus hispidus are sympatric species in the Brazilian semiarid region. Despite being considered interesting models for ecological studies, little is known about basic aspects of their biology, such as hematological parameters. Thus, the objective of this work was to perform the differential count of leukocytes and describe the morphometry of erythrocytes and leukocytes in these two species of lizards, with emphasis on hemoparasitism by intracellular protozoa. For this, 30 specimens (15 A. ocellifera and 15 T. hispidus) were used for analysis. After making the slides, a differential count of 100 leukocytes per slide was performed. In addition, 20 erythrocytes and 15 leukocytes were photographed per slide for morphometric analysis. The measurements were measured for the parameters area, perimeter, maximum and minimum axes, with the ellipse formulas used for area and perimeter. Interspecific and intraspecific differences (parasitized and non-parasitized lizards) were tested for erythrocyte morphometric parameters, erythrocyte nucleus and leukocytes. The differential count showed that heterophiles were the predominant cell type for both species of lizards, while basophils were the least abundant for A. ocellifera and eosinophils for T. hispidus. As for leukocyte measurements, only the monocyte differed significantly between species, greater in A. ocellifera, and intraspecifically only for the minimum axis parameter, greater in parasitized T. hispidus. Erythrocytes differed between species in terms of cell and nucleus size, being higher in T. hispidus. Among the hemoparasites, found only in T. hispidus, Plasmodium sp. caused more discrete changes in the erythrocyte, while Hepatozoon sp. caused marked macrocytosis and hypochromia in these cells. In general, there does not seem to be a relationship between the differential leukocyte count and hemoparasitism.